Drowning : the rescue of Flight 1421 : a novel - Newman, T. J. (Novelist) (Avid Reader Press, 2023)
When Flight 1421 crashes into the ocean six minutes after take-off, the surviving passengers believe they are the lucky ones until the plane starts to sink to the ocean floor, trapping them inside, and they must wait to be rescued as both air and time run out.